Media Video Animasi Interaktif Berpendekatan Kontekstual Pada Mata Pelajaran IPAS Siswa Kelas IV SDN 5 Kampung Baru - Bagus Robiansyah; I Nyoman Jampel; Dewa Gede Agus Putra Prabawa (Jurnal Media dan Teknologi Pendidikan, 2025)
Students often face difficulties in understanding abstract concepts because learning materials are not sufficiently connected to real-life contexts and there is a lack of interactive media. This study aims to develop and analyze the effectiveness of interactive animated video media with a contextual approach in IPAS (Science and Social Studies Integration) learning for fourth-grade elementary school students. The Hannafin and Peck development model was applied in three stages: needs analysis, design, and development and implementation. Data were collected through tests, observations, and interviews, and analyzed using descriptive quantitative, qualitative, and t-test techniques. The research subjects included content experts, design experts, media experts, and students for individual, small group, and field trials. The results show that the developed media are valid and effective in improving students’ conceptual understanding and learning outcomes. The interactive animated video media with a contextual approach effectively creates more meaningful, engaging, and relevant learning experiences related to students’ daily lives. The use of this media can help teachers integrate IPAS learning with real-life contexts, thereby enhancing student engagement and learning motivation. Furthermore, this media serves as an innovative technology-based learning alternative that supports the implementation of the Merdeka Curriculum and strengthens the Pancasila Student Profile through active, creative, and reflective learning.